Consumer response to state-of-origin labels: the moderating role of residency. Issue 7 (23rd July 2020) - Jung, Jae Min; Jones, Joseph; Haugtvedt, Curtis P.; Banerjee, Somnath
Abstract : Purpose: Despite the large number of studies on country of origin, little is known about the effects of state-level product origin information on consumer attitudes and purchase intentions. Likewise, little is known about when the state-of-origin (SOO) information enhances, has no effect or has a negative effect on consumer attitudes and purchase intentions. Primarily drawing on the country-of-origin literature, this study aims to examine the influence of SOO label information and the moderating role of state residency. Design/methodology/approach: To test five hypotheses, the authors conducted a survey (Study 1) and an experiment (Study 2). The analyses included content analysis, regression and ANOVA. Findings: The findings show that for certain products, moderate-to-strong product–state associations exist. However, when the associations are weak, consumers show bias for products made in their (vs other) states. The findings also show that when consumers evaluate their state products, normative (vs cognitive) reasons drive their attitudes, but that when they assess products from states other than their state of residency, cognitive (vs normative) reasons drive attitudes. Additionally, economic sustainability seems a powerful motivator for buying products made in their state of residency. Practical implications: Companies should take advantage of positive biases for their products in the states in which they produce products. However, when companies market their products outside their states of production, in some cases, they should consider deemphasizing SOO information unless there is a strong product–state association present among consumers outside of the state. Originality/value: This paper adds value by providing new insights for designing product origin labeling programs. Suggestions for future research and marketing strategies for practitioners who want to use SOO as a branding strategy are offered.